Molecular cloning and bioactivity of an IL-2 homologue in large yellow croaker (Larimichthys crocea). Issue 81 (October 2018) - Mu, Pengfei; Wang, Yuhua; Ao, Jingqun; Ai, Chunxiang; Chen, Xinhua
Abstract: Interleukin-2 (IL-2), an important immunomodulatory cytokine, plays a crucial role in promoting the proliferation, activation and differentiation of T cells. Here, the cDNA of an IL-2 homologue ( Lc IL-2) in large yellow croaker ( Larimichthys crocea ) was cloned by RACE-PCR techniques. The open reading frame (ORF) of Lc IL-2 gene is 426 bp long and encoded a precursor protein of 141 amino acids (aa), with a 20-aa signal peptide and a 121-aa mature peptide containing two putative N-glycosylation sites at Asn 77 and Asn 101 . The Lc IL-2 is preferentially expressed in lymphocytes-rich tissues, such as spleen and blood, and is increased in head kidney and spleen upon inactivated trivalent bacterial vaccine or poly(I:C) stimulation. Lc IL-2 expression could also be detected in primary head kidney leukocytes (PKL), primary head kidney macrophages (PKM) and primary head kidney granulocytes (PKG), with the highest level in PKL. In addition, the expression level of Lc IL-2 in PKL was slightly induced by LPS or poly(I:C), while markedly induced by PHA or Con-A. The recombinant Lc IL-2 protein produced in Pichia pastoris could increase the expression of genes involved in Th1 (IL-2, IFN-γ and T-bet) and Th2 (IL-4/13A, IL-4/13B and GATA3) development and differentiation, and of the IL-2 downstream transcription factor STAT5B gene, but inhibit the expression of genes related to Th17 (IL-17A/F2 and IL-17A/F3) development and differentiation. Taken together, our results indicated that Lc IL-2 possesses similar structural and functional characteristics to other vertebrate IL-2s, and may play a role in T cell development and differentiation. Highlights: An IL-2 homologue was characterized in large yellow croaker. The Lc IL-2 expression was slightly induced by LPS or poly(I:C), while markedly induced by PHA or Con-A. r Lc IL-2 could increase the expression of genes involved in Th1, Th2 development and differentiation. r Lc IL-2 could inhibit the expression of genes related to Th17 development and differentiation. The Lc IL-2 may play a role in T cell development and differentiation.